A Novel Method for Manufacturing Molds for CFRP Prepreg Lamination Using Polymeric Acrylic Resin–Aluminum Trihydrate - Mihai Părpăriță; Paul Bere; Mircea Cioază (Journal of Manufacturing and Materials Processing, 2025)
In the composite materials industry, the fabrication of complex parts often necessitates the use of specialized tools, such as milled molds with intricate geometries. Among these, machined aluminum molds are widely regarded as effective tools for laminating CFRP (Carbon Fiber Reinforced Polymer) prepreg materials. However, the cost and time associated with machining aluminum molds can be significant. This paper presents a novel method for manufacturing molds using polymeric acrylic resin combined with aluminum trihydrate material (commercially known as DuPont Corian materials), offering a potential alternative with reduced complexity and cost. The study investigates the influence of various milling parameters, such as tool speed, tool type, feed rate, and depth of cut on the mechanical properties and surface finish of the molds. Also, laminating tests are conducted; results indicate that laminating tools produced through this method achieve competitive mechanical performance, including a hard, smooth surface with low roughness, making them viable candidates for industrial use. The proposed approach is particularly beneficial in terms of reducing machining time and overall costs while maintaining the necessary precision and durability for high-performance applications. This method, therefore, represents a promising solution for manufacturers seeking to optimize mold production processes in the composite materials industry.